(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
A 12 year old boy with Marfan syndrome associated with severe mitral regurgitation underwent successful mitral valve replacement. Careful evaluation of the cardiovascular system and specific surgical intervention help long-term survival of patients.